Design and Performance Evaluation of an FPV Tactical Loiter Munition Drone for Tropical Mountainous Operations in Papua - Gede, Gede Dedik Suprapto; Ferdinand Hasudungan Siagian; Oktaheroe Ramsi (Langit Biru: Jurnal Ilmiah Aviasi, 2026)
This research aims to design and analyze an FPV Tactical Loiter Munitions (FPV-TLM) drone as a tactical operational support platform for the Indonesian Army (TNI AD) in the Papua region. The FPV-TLM technology serves a dual function as both a reconnaissance system and a precision-strike asset capable of operating in extreme environments. The study employs a descriptive-qualitative approach combined with limited-scale experimental testing to evaluate control-system stability, energy efficiency, and surveillance effectiveness in tropical and mountainous terrain. The test results indicate that the adaptive PID-based control system maintained hover stability up to 93% under wind speeds of 10-14 m/s. The Kevlar-Nylon variant was identified as the most optimal configuration, achieving an average loiter duration of 35.2 minutes and an energy efficiency of 0.78 Wh/min. Strategically, the use of FPV-TLM enhances surveillance operational effectiveness by 47% compared to conventional ground patrols and supports national defense self-reliance through increased domestic content (TKDN) and integration of local research.